A potential polymer formulation of a durable carbon-black catalyst with a significant fuel cell performance over a wide operating temperature range. (December 2018) - Berber, Mohamed R.; Fujigaya, Tsuyohiko; Nakashima, Naotoshi
Abstract: Polymer electrolyte membrane fuel cells (PEMFCs) that quickly operate at relatively low temperatures, while generating a high-power output is of particular interest, especially for portable devices, since no external power source is required to reach the highest power at higher operating temperatures. Here, we describe the temperature-dependence and the performance of a membrane electrode assembly (MEA) of a newly fabricated fuel cell catalyst of carbon black (CB) which was functionalized for the first time by two conductive polymers; i.e., polybenzimidazole and Nafion. The fabricated MEA quickly operated at room temperature, providing a power density of 130 mW/cm 2 (172 mW/mgPt) and 174 mW/cm 2 (230 mW/mgPt) under 50% RH and 100% RH conditions, respectively. It also showed a remarkable durability (900-h long-term durability testing and 100, 000 potential-stress cyclings) with a maximum power density of 250 mW/cm 2 (330 mW/mgPt) at 60 °C. The electrochemical impedance spectroscopy (EIS) analysis showed an enhanced ionic conductivity of the assembled MEA at low temperatures due to the fabrication design which provided more useful conductive pathways for the smooth proton transport on the polymer's backbone. The results of this research satisfies the market demands, and offer reasonably priced materials with a remarkable performance and durability. In addition, it will stimulate industrial researchers to be involved in similar activities. Graphical abstract: Highlights: Advanced formulation of fuel cell catalysts. Double-polymer-coated carbon black with high fuel cell performance. Highly durable catalyst at low operating temperatures and a low humidity levels. Wide operational temperature range of fuel cells.